Differentiating the subtypes of social anxiety disorder. (November 2013) - Dalrymple, Kristy; D'Avanzato, Catherine
Since the inclusion of subtypes of social anxiety disorder (SAD) in the DSM-III-R, the most studied have been generalized versus specific subtypes. Previous research indicated that the generalized subtype was associated with greater severity, comorbidity and functional impairment compared to the specific subtype, but more recent evidence supports a dimensional conceptualization of SAD. Earlier studies also possessed limitations, such as heterogeneity in definitions of generalized SAD. Based on the more recent findings and the limitations of the earlier studies, the DSM-5 eliminated the generalized specifier. However, it also retained a categorical system by including a performance-based fear specifier, thus leaving an open debate on whether or not a dimensional or categorical system best describes SAD. Future research could examine other, more recent concepts as potential subtypes (e.g., attentional biases), or perhaps the larger question of the overall utility in subtyping SAD.